One polymorphism at the Stearoyl CoA Desaturase (SCD) gene is associated to CLA content of sheep milk fat - Antonello Carta; Annalisa Pernisa; Tiziana Sechi; Mario Graziano Usai; Sabrina Miari (Italian Journal of Animal Science, 2010)
On OAR 22 a highly significant QTL affecting the rate of desaturation of vaccenic acid (VA) to conjugated linoleic acid (CLA) in the mammary gland of sheep was found segregating on four dairy sheep families of a Sardinian x Lacaune back-cross population. The most likely location of the QTL was 35 cM corresponding to Stearoyl CoA Desaturase (SCD) gene location on the Australian Sheep Gene Map. The aim of this work was finding mutations along the SCD gene associated with the CLA/VA variability in sheep milk. The sequencing of a large part of the gene in the four informative sires allowed identifying one SNP in intron 4 (3295 C>T relative to Capra hircus SCD gene, GenBank Acc. no. AH011188). The sequencing of high and low phenotypic tails’ progeny from the most significant family showed a strong association of the found mutation with the CLA/VA variability.